2011
DOI: 10.1038/nature10130
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor blockade at rest triggers rapid behavioural antidepressant responses

Abstract: Clinical studies consistently demonstrate that a single sub-psychomimetic dose of ketamine, an ionotropic glutamatergic n-methyl-d-aspartate receptor (NMDAR) antagonist, produces fast-acting antidepressant responses in patients suffering from major depressive disorder (MDD), although the underlying mechanism is unclear1-3. Depressed patients report alleviation of MDD symptoms within two hours of a single low-dose intravenous infusion of ketamine with effects lasting up to two weeks1-3, unlike traditional antid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

128
1,733
14
22

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,658 publications
(1,897 citation statements)
references
References 32 publications
128
1,733
14
22
Order By: Relevance
“…Since the delay to reach efficacy with current antidepressants is a major drawback, particularly for suicide risk patients, the development of fast-acting antidepressants represents a significant advance for the treatment of depression [7]. Interestingly, in recent preclinical and clinical reports ketamine emerges as a novel rapid-acting antidepressant agent [8][9][10]. However, the mechanisms of action implicated in the ketamine antidepressant-like effect are not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Since the delay to reach efficacy with current antidepressants is a major drawback, particularly for suicide risk patients, the development of fast-acting antidepressants represents a significant advance for the treatment of depression [7]. Interestingly, in recent preclinical and clinical reports ketamine emerges as a novel rapid-acting antidepressant agent [8][9][10]. However, the mechanisms of action implicated in the ketamine antidepressant-like effect are not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fast-acting antidepressants are urgently needed for clinical treatment of depression. Autry et al reported in a recent issue of Nature that N-methyl-D-aspartate receptor (NMDAR) antagonists could be such candidates by triggering rapid behavioural antidepressant responses [4] .…”
mentioning
confidence: 99%
“…These results are consistent with previous studies [12,13], in which (R)-ketamine appeared to be a more potent, long-lasting, and safe antidepressant than (S)-ketamine. MK-801, another NMDAR antagonist, also has rapid antidepressant effects but they are not maintained [14,15]. These findings raise doubts about the NMDAR-dependent antidepressant responses to ketamine.…”
mentioning
confidence: 99%
“…The antidepressant effects of ketamine require the activation of several intracellular signaling pathways [15,23,24] and the enhancement of AMPAR-mediated synaptic plasticity [20,25]. The authors examined the biochemical profiles of ketamine and (2R,6R)-HNK in the hippocampus and medial prefrontal cortex, two moodrelated brain regions.…”
mentioning
confidence: 99%